Chapter Simulazione incarnata, estetica e architettura: un approccio estetico sperimentale - Gattara, Alessandro (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2021)
This chapter, written by a cognitive neuroscientist and an architect, endeavors to suggest why and how cognitive neuroscience should investigate our relationship with aesthetics and architecture-framing this empirical approach as experimental aesthetics. The term experimental aesthetics specifically refers to the scientific investigation of the brain-body physiological correlates of the aesthetic experience of particular human symbolic expressions, such as works of art and architecture. The notion "aesthetics" is used here mainly in its bodily connotation, as it refers to the sensorimotor and affective aspects of our experience of these particular perceptual objects.